1980
DOI: 10.1104/pp.65.6.1103
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, Leaf Resistances, and Ribulose-1,5-Bisphosphate Carboxylase Degradation in Senescing Barley Leaves

Abstract: The relationship between loss of ribulose-1,5-bisphosphate carboxylase (RuBPCase) and the decline in photosynthesis during the senescence of barley primary leaves was assessed. Loss of RuBPCase accounted for about 85% of the decrease in soluble protein. The senescence of leaves is usually associated with loss of soluble protein, predominantly RuBPCase2 (5,12,13,21, 25, 26).Protein degradation and remobilization provide an important source of N and S for other parts of the developing plant (4, 21). The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(90 citation statements)
references
References 20 publications
7
81
2
Order By: Relevance
“…Although loss of Chl is a commonly observed symptom of senescence, Chl frequently disappears most slowly during senescence among the photosynthetic components (11,12,14,21). As shown in Figure 4, low irradiance strongly retarded the decline in the Chl content and it remained almost constant until late senescence.…”
Section: No Apparent Decline In Chimentioning
confidence: 90%
“…Although loss of Chl is a commonly observed symptom of senescence, Chl frequently disappears most slowly during senescence among the photosynthetic components (11,12,14,21). As shown in Figure 4, low irradiance strongly retarded the decline in the Chl content and it remained almost constant until late senescence.…”
Section: No Apparent Decline In Chimentioning
confidence: 90%
“…Analysis of photosynthetic processes revealed that carbon fixation rates declined progressively from the time of full leaf expansion (Figure 4). This age-related, progressive loss of photosynthetic function from the time of leaf maturity may be a general feature of annual plants because this phenomenon has been observed in cucumber (Callow, 1974), Perilla (Batt and Woolhouse, 1975), barley (Friedrich and Huffaker, 1980), wheat (Peoples et al, 1980), maize (Crafts-Brandner et al, 1984a), and soybean (Wittenbach, 1982;Ford and Shibles, 1988). Wittenbach referred to the photosynthetic decline as "functional senescence" to distinguish this process from the subsequent rapid loss of chlorophyll and macromolecular turnover associated with the senescence syndrome (Wittenbach, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Rubisco accounts for 12% to 30% of total leaf protein in C 3 species (Evans, 1989). The degradation of Rubisco and most other stromal proteins begins at an early stage of senescence, and the released nitrogen can be remobilized to growing organs and finally stored in seeds (Friedrich and Huffaker, 1980;Mae et al, 1983). In addition, these proteins are also degraded under carbon-limited conditions, which are caused by darkness (Wittenbach, 1978), and their carbon is used mainly as substrates of respiration.…”
mentioning
confidence: 99%